Strategi Negosiasi Efektif dalam Mengelola Konflik Konstruktif di Organisasi Pendidikan - Mainur Andriya; Salfen Hasri; Sohiron; Umi Iriani (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
Effective negotiation strategies are essential in managing conflicts within educational organizations. This paper explores two primary negotiation strategies—integrative negotiation and participative leadership—that play pivotal roles in conflict resolution. Integrative negotiation focuses on finding mutually beneficial solutions, emphasizing the importance of understanding the underlying interests of all parties involved, fostering long-term relationships, and promoting cooperation. On the other hand, participative leadership encourages active involvement from all members in the decision-making process, creating a sense of shared responsibility and ownership. This approach not only facilitates conflict resolution but also enhances creativity, trust, and commitment among stakeholders. Both strategies, when applied effectively, contribute to a more harmonious and productive environment, enabling educational organizations to achieve their collective goals. The combination of integrative negotiation and participative leadership offers a comprehensive framework for conflict management, fostering a culture of collaboration and mutual respect within the organization.